Effect of ZrC particle distribution on the ablation resistance of C/C-SiC-ZrC composites fabricated using precursor infiltration pyrolysis. Issue 10 (July 2020) - Wu, Xiaowei; Su, Zhean; Huang, Qizhong; Tong, Kai; Xie, Xiangmin; Zeng, Chen
Abstract: C/C-SiC-ZrC composites with different ZrC distributions were fabricated using precursor infiltration pyrolysis combined with different drying processes. The microstructural and ablation resistance properties of the composites with different ZrC distributions were investigated. For the C/C-SiC-ZrC composites fabricated using conventional heating-drying, where ZrC particles were largely agglomerated into islands with a dimension range of 10–20 μm, the mass and linear ablation rates under a plasma flame for 60 s were 0.558 mg/s and 16.33 μm/s, respectively. By contrast, for the composites fabricated using freeze-drying, where isolated ZrC particles with a size range of 200–300 nm were uniformly dispersed in the matrix, the mass and linear ablation rates were only 0.078 mg/s and 14.20 μm/s, respectively. This difference in the distribution of ZrC particles led to the difference in ablation resistances, as the uniformly distributed fine ZrC particles were easily oxidized and well dispersed in SiO2 molten glass, which increased the viscosity of the molten glass layer. The high-viscosity SiO2 -ZrO2 molten layer covering the surface of the composites effectively prevented the penetration of oxygen and resisted the scour of airflow.